EVALUASI PEMILIHAN JASA PENGIRIMAN BAGI PELAKU BISNIS ONLINE DI BIDANG FASHION - , VEERA LAKHSMI, Anna Maria Sri Asih, S.T., M.M., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The rapid development of online business has challenged the online business performer to fulfill their customersâ needs. One activity that needs to be concerned by the online business performer to maintain its reputation and reach a bigger target market is the freight shipping service. This research is conducted to determine the criteria and its weight of the freight shipping service in Indonesia (PT. Pos Indonesia, PT. Citra Van Titipan Kilat (TIKI), and PT. Jalur Nugraha Ekakurir (JNE)) that should be considered by the online business performer in the fashion industry. The criteria and weight is gathered by using AHP method. The weight obtained from each shipping service will be used to decide the rating of each shipping service company. The rating is used as a basic in determining the rank of the service. The author compares the performance gap of each company towards the ideal performance of its competitors by using the Improvement Gap Analysis (IGA) method to give a recommendation of improvement that can be performed by each freight shipping company. The output of this research shows that there are five criteria and its weight that can be considered by the online business performer in choosing the freight shipping service, such as punctuality (0.30), company reputation (0.25), warranty (0.21), convenience (0.15), and price (0.10). According to the results on those criteria PT. Citra Van Kilat is ranked first as the best performance freight shipping service company with 0.80 value of weight. PT. Pos Indonesia occupies the second position with 0.66 value of weight, and PT. Jalur Nugraha Ekakurir states the lowest value of weight at 0.58 and makes it occupies the third position.